Rancang Bangun Turbin Angin Sumbu Horizontal 3 Blade Menggunakan PVC - Firman Firman; Jumadi Tangko; Saharuddin Nara; Ardiansyah Ardiansyah (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
With the increasing need for electrical energy today, resulting in the use of fossil fuels also increasing and in line with its development, the use of fossil fuels will experience shrinkage, therefore other alternative energy is needed to overcome the decreasing fossil fuels. One form of energy that exists in nature is wind. Therefore, wind turbines are starting to be used as alternative energy. The purpose of this design is to determine the performance of a 3-blade horizontal axis wind turbine and to determine the effect of wind speed on turbine rotation, output power and efficiency generated by the wind turbine. The design method is to design a horizontal axis wind turbine using 3 blades of PVC material with a diameter of 182 cm. The results of the wind turbine design show the theoretical data at the highest wind speed of 7.3 m/s with 606.92 watts of wind power generated. In these conditions it can be seen that the wind speed and blade diameter greatly affect the output power of the design results.